2015
DOI: 10.3748/wjg.v21.i36.10348
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic sleeve gastrectomy and gastroesophageal reflux

Abstract: Bariatric surgery is the only effective procedure that provides long-term sustained weight loss. Sleeve gastrectomy (SG) has emerged over the last few years to be an ideal bariatric procedure because it has several advantages compared to more complex bariatric procedures, including avoiding an intestinal bypass. However, several published follow-up studies report an increased rate of gastroesophageal reflux (GERD) after a SG. GERD is described as either de novo or as being caused by aggravation of preexisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
111
2
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(124 citation statements)
references
References 71 publications
3
111
2
8
Order By: Relevance
“…Some publications of world literature indicated this range as 3-21%. [19,20] Our gastroesophageal reflux rate seems reasonable when compared with the reported results.…”
Section: Discussionsupporting
confidence: 80%
“…Some publications of world literature indicated this range as 3-21%. [19,20] Our gastroesophageal reflux rate seems reasonable when compared with the reported results.…”
Section: Discussionsupporting
confidence: 80%
“…A hiatal hernia is present in approximately half of obese patients [5,12]. Hiatal hernia not only exacerbates reflux symptoms but also may lead to the incomplete removal of the gastric fundus during SG [3].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is one of the most important health problems in developed and developing countries [1][2][3]. Morbid obesity is defined as a body mass index (BMI) of more than 40 kg/m².…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, although we are not against HHR during LSG, we suggest focus be directed to contouring of the sleeved stomach to prevent de novo GERD after LSG, because it is our point of view that the primary mechanism of de novo GERD after LSG is a lack of gastric compliance and increased intraluminal pressure caused by gastric fundus removal. Stenard and colleagues suggested that final shape of the sleeve affects the incidence of de novo GERD (e.g., narrowing, twisting, and dilatation of the sleeve stomach) [6]. In this regards, our focus in performing LSG was on three anatomical points: 1) fixation of the sleeved stomach in retroperitoneal or mesocolic fat; 2) a wider distance stapling to avoided narrowing the gastric angle; and 3) antral plication (rather than resection) for minimize delayed gastric emptying.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have been performed on conversion LSG to gastric bypass due to intolerable GERD after LSG [2][3][4][5], and many suggestions have been made regarding the cause of GERD [6]. High intraluminal pressure from narrow tube-like stomach with an intact pylorus sphincter play a major role in the development of GERD or a low esophageal sphincter complex (e.g.…”
Section: Introductionmentioning
confidence: 99%